Speculative Creation of Vedic Hymns: Hermeneutic Approach to the Selected Verse - Ghimire, Surendra (BMC Journal of Scientific Research, 2018)
The article, specifically, aims to make a knowledge contribution in epistemology, especially intuition and speculation two approaches of knowledge making. At the same time, it engages into Vedic study by revealing the process of creating the hymns and verses that are compiled in the texts. Some selected verses from the Rigveda translated by Ralph Thomas Hotchkin Griffith (1896) were taken as a source of information. Conceptual analysis of these verses and hymns suggests a pattern which indicates that these were created skeptically rather than authoritatively, and synthesized with microcosm-macrocosm analogy. On the other hand, there is no evidence of intuitive approach of creating the verses. Since an argument- ’the knowledge was created speculatively by the then scholars not intuitively by the seers’ is put forward. Hence, the paper demystifies the mystified knowledge surpassing the blasphemy of Veda, against the faith of uncreated religio-philosophical text the hermeneutic interpretation presents, as a reflective and scholarly act, an opposite epistemological perspective.